Biochemical and biomechanical drivers of cancer cell metastasis, drug response and nanomedicine. Issue 9 (September 2016) - Yoshii, Tatsuyuki; Geng, Yingying; Peyton, Shelly; Mercurio, Arthur M.; Rotello, Vincent M.
Highlights: Biomolecules including integrins are key factors in cancer progression. Nanomaterials provide tools for regulating the chemical environment of cells. Mechanobiology is an emerging determinant in designing cancer therapies. Abstract : Metastasis, drug resistance and recurrence in cancer are regulated by the tumor microenvironment. This review describes recent advances in understanding how cancer cells respond to extracellular environmental cues via integrins, how to build engineered microenvironments to study these interactions in vitro and how nanomaterials can be used to detect and target tumor microenvironments.